Green Campus Initiative Assessing Waste Management at a Technical Polytechnic: Inisiatif Kampus Hijau Mengkaji Pengelolaan Sampah di Politeknik Teknik - Adityo Haryo Bismoko; Rini Mulyani; Eva Rita; Nasfryzal Carlo; Lusi Utama (Academia Open, 2024)
Background: Effective waste management is pivotal for establishing eco-friendly educational environments, guided by global sustainability standards. However, many institutions face challenges in aligning their practices with these environmental benchmarks. Knowledge Gap: Research often highlights the necessity of holistic waste strategies but lacks specific assessments of waste management within the context of Green Campus initiatives, especially in vocational education settings. Aims: This study aims to evaluate current waste management practices at a technical polytechnic, assessing their effectiveness and compliance with established green standards. Results: The evaluation reveals that the institution's waste management initiatives are significantly lacking, with a total score of only 75 out of a possible 1800 points. The polytechnic performs poorly in recycling and processing various waste types, although there is modest progress in reducing paper and plastic use. Novelty: This research introduces a novel application of global sustainability standards to assess waste management practices at a vocational higher education institution, highlighting specific areas of inefficiency and their broader implications. Implications: The findings emphasize the critical need for comprehensive recycling programs, improved waste segregation, and increased community involvement in sustainability efforts. These improvements are crucial for both environmental benefits and enhancing the institution's standing in global educational rankings that prioritize sustainability. Highlights: Enhance Recycling: Implement robust recycling programs to meet global sustainability standards. Improve Segregation: Develop better waste segregation and processing practices. Boost Community Involvement: Engage the campus community actively in sustainability efforts. Keywords: Waste Management, Green Campus, Recycling, Environmental Education, UI GreenMetric